Cooling Ability of Smooth and Dimpled Surfaces determined by Experiment and Numerical Simulation - Dobsakova, Lenka; Duy Nguyen, The (Manufacturing Technology Journal, 2023)
The study of the cooling process of a gun barrel is of great importance in the field of ballistics and weaponry. This is because the cooling process directly impacts the gun's accuracy, precision, and longevity. To minimize these effects, the geometry of the barrel is optimized, among other things. The article examines the cooling process of the copper plate and barrel with a structured surface. The study aims to determine the structured surface's effects on heat transfer through radiation and convective components. The work focuses on conducting experiments and numerical simulations to observe and evaluate the cooling process of the studied objects in the environment. The results of experiments and numerical simulations were compared to find out the possibility of substitution of experimental measurement by numerical simulation even I n so difficult flow conditions.
Keywords: Structured surface; Barrel; Heat Transfer; Dimple; Numerical simulation